Development of MoS2-CNT composite thin film from layered MoS2 for lithium batteries - COLEMAN, JONATHAN NESBIT (My University, 2013)
Organic thin film nanocomposites, prepared by liquid- phase exfoliation, were investigated for their superior electrical properties and thermoelectric behavior. Singlewalled carbon nanotubes (SWNT) were stabilized by intrinsically conductive poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) in an aqueous solution. The electrical conductivity (r) was found to increase linearly as 20 to 95 wt % SWNT. At 95 wt % SWNT, these thin films exhibit metallic electrical conductivity ( 4.0 105 S m 1) that is among the highest values ever reported for a free-standing, fully organic material. The thermopower (S) remains relatively unaltered as the electrical conductivity increases, leading to a maximum power factor (S2r) of 140 lW m 1 K 2. This power factor is within an order of magnitude of bismuth telluride, so it is believed that these flexible films could be used for some unique thermoelectric applications requiring mechanical flexibility and printability.
PUBLISHED
Keywords: Singlewalled carbon nanotubes